Transport of dangerous goods by road from a European aspect - Zbigniew ŁUKASIK; Aldona KUŚMIŃSKA-FIJAŁKOWSKA; Jacek KOZYRA (Scientific Journal of Silesian University of Technology. Series Transport)
Transport plays an important role in national economies and impacts on economic development. The scale of the transportation of goods that may be dangerous to humans and the environment is expanding every year. Overall, transport is dangerous for the environment and road users, causing the increased emission of pollutants, accidents and traffic collisions. The rise in demand of basic materials, such as petrol and diesel, has led to a growth in the transport of dangerous goods, which in turn has increased the risk of road accidents. The research method used in this article involves an analysis of the inspection rates regarding the transport of dangerous goods by road in the EU and related legal documents.